Assessment of household awareness of, attitude to and practice of environmental sanitation exercise and waste disposal management in Oondo city, Ondo State (2018)
The study identified the gap in household awareness of, attitude to and practice of waste disposal system and environmental sanitation exercise in Ondo city, Ondo state. The survey was conducted using 660 respondents. A self-constructed questionnaire with a Cronbach Alpha Reliability co-efficient of 0.71 (household awareness), 0.79 (house attitude) and 0.80 (household practice) was used for the study. An observation checklist was also used to elicit information. SPSS version 21.0 was used for percentage, mean, and standard deviation. It revealed householders have low level of awareness of waste management system, moderate attitude to environmental sanitation and poor waste disposal system as well as moderate practice. It is therefore, important for all and sundry across profession and divides in Nigeria, most especially in Ondo city to realize the importance of taking care of their environment in terms of sanitation and proper waste disposal method. The study recommended that there is need for “culture of waste disposal skills” which individuals should imbibe for a suitable environmental living via symposium, health talk and seminars across profession. It also recommended staunch punishment for environmental law breakers. There is need for sign post, bill boards and other media which should bear “Pro-bono” information and its penalties at market areas, streets and other crucial areas to caution excesses in Ondo city.